Strategy without tactics is the slowest route to victory. Tactics without strategy is the noise before defeat. A comparative study of the Malayan Emergency 1948 to 1960 and the Rhodesian Civil War 1964 to 1979 - Stack, Michael David Leonard (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.